Pengaruh Penerapan E-Goverment, Transparansi dan Maturitas Sistem Pengendalian Internal (SPI) Terhadap Kualitas Laporan Keuangan Pemerintah Kabupaten Buleleng - Suryani, Ketut Yuni; Prayudi, Made Aristia; Astawa, I Gede Putu Banu (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the effect of e-government implementation, Transparency and Maturity of Internal Control System (SPI) on the Quality of Buleleng Regency Government Financial Reports. The research method uses a quantitative approach with a survey method through the distribution of questionnaires to 74 respondents consisting of heads of financial sub-sections and financial report preparation staff at 37 Regional Work Units (SKPD) in Buleleng Regency. The sampling technique uses purposive sampling. Data are analyzed using multiple regression with the help of SPSS 26. The results of the study indicate that the e-government variable does not have a significant effect on the quality of Buleleng Regency government financial reports. Meanwhile, the Transparency and Maturity of Internal Control System (SPI) variables have a positive and significant effect on the quality of Buleleng Regency government financial reports. This finding indicates that the higher the level of implementation of transparency and maturity of the internal control system (SPI), the better the quality of local government financial reports. However, the implementation of e-government has not yet made a significant contribution, possibly due to the suboptimal implementation of the reporting system, which focuses solely on service and administration, and the limited use of technology by human resources. Therefore, the Buleleng Regency government is expected to improve the effectiveness of its e-government implementation and continue to strengthen the transparency and maturity of its internal control system (SPI) to improve the quality of its financial reports. Keywords: E-Government, Transparency, Internal Control System Maturity, financial report quality